The life and adventures of Santa Claus - Baum, L. Frank (Lyman Frank), 1856-1919.; Clark, Mary Cowles (New York : Greenwich House : Distributed by Crown Publishers, 1983)
Describes the life of Santa Claus from birth through old age and into immortality.
Keywords: Santa Claus -- Fiction; Christmas -- Fiction